EFFECTIVE MATERIALS MANAGEMENT FOR INCREASING PRODUCTIVITY - Sehgal, Karan; Pratap, Anuj; Kuhar, Ravi (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
One of the problems facing Manufacturing Company is the growing trend towards the higher cost of materials and services and constant shut down of factory erode. The paper focuses on how business firm can attain profitability through effective management of materials. The objective of this paper is to identity problems of material management, which if corrected can result in profitability. The paper also examines and outlines the roles and benefits of materials management. The finding shows that there is need to recognize the materials management function and it has been suggested that for a firm to achieve profitability, the goal of materials management outlined in this paper should be properly carried out.